A Comparison of Two Process Tracing Methods for Choice Tasks - Lohse, Gerald L.; Johnson, Eric J. (Organizational behavior and human decision processes, 1996)
Process tracing methods, particularly those based on information acquisition, are becoming commonplace. Because of this, it is important to examine both the reactivity and the validity of these techniques. This research compares information acquisition behavior for choice tasks using Mouselab, a computerized process tracing tool, and Eyegaze, an eye tracking system. In an experiment using apartment selection tasks and gambles, we found significant differences contingent upon the process tracing method for 10 process tracing measures including subsequent choices. Computerized process tracing tools increase the amount of time needed to acquire information compared with eye tracking equipment. As a result, subjects using Mouselab tend to have more systematic information acquisition behavior than that observed with eye tracking equipment. Additional research is needed to explore the magnitude and consequences of these differences.